Les valeurs de la science Enquête sur les réformes de l'évaluation de la recherche en France - Gozlan, Clémentine (Éducation et savoirs en société, 2020)
Over the past 20 years, the world of higher education and research has undergone an unprecedented series of reforms. Through an empirical survey based on interviews, archives and observation, this book provides an overview of the academics who have been involved in the reform of standards in the scientific profession in a scientific evaluation body, the AERES. What knowledge do they use to draw up new evaluation criteria? To what extent do these standards redefine what "conducting research" means today? What challenges do these changes pose in the humanities and social sciences? Going behind the scenes at a controversial agency, this book sheds new light on the current changes in the governance of the scientific community, while rekindling debate on science, and its place and value in our society. It is intended for academics who are interested in the sociology of science, public policy or professions, but also more broadly for students and scientists who question the evaluation tools they have to contend with on a daily basis.